Humanized department: Nursing behaviors in Primary Health Care (Research, Society and Development, 2021)
Objective: to describe how nurses' behavior in PHC helps in the humanization of childbirth. Methodology: it is a descriptive and qualitative field research. The entire protocol carried out in the research was approved by the ethics committee on research with human beings under number 2,935,584. The total number of participants was 10 nurses working in the FHS of the municipality of Piripiri Piauí. Results: through data analysis, some similar points were highlighted, which stood out in 4 categories: understanding of humanization by nurses; nursing behavior in face of the humanization of childbirth in PHC; barriers identified in the process of humanizing childbirth in PHC and the nurse's duties in PHC regarding the humanization of childbirth. The results show that the nurse who works in the ESF assumes, among the different attributions, the role of responsible for the prevention, promotion and rehabilitation of the individual. The act of caring is relevant for actions planned in a different way, in which interventions are carried out in a humanized way. Conclusion: Thus, it is concluded that the health professional exerts an important influence on women during pregnancy, especially in prenatal care, as it is a time when the professional must be guiding the pregnant woman about the entire gestational process and as to the type of delivery.